The effect of extraction methods on fatty acid and carotenoid compositions of marine microalgae Nannochloropsis oculata and Chaetoceros gracilis - Loh, Su Peng; Lee, S. P. (Universiti Putra Malaysia Press, 2013)
This study was conducted to assess three extraction methods for the determination of fatty acid compositions and carotenoids (lutein, zeaxanthin, ÃŸ-carotene, and a-carotene) from marine microalgae, Nannochloropsis oculata (NO) and Chaetoceros gracilis (CG). For this purpose, three different extraction methods for the determination of fatty acids (dichloromethane:methanol, water:propan-2-ol:hexane and direct saponification-ethanol KOH) and carotenoids (hexane:ethanol:acetone:toluene, methanol:chloroform and methanol:tetrahydrofulran) were used. Two derivatization methods using different types of catalyst (acetyl chloride and boron trifluoride) were also used for the transmethylation of the fatty acids into corresponding methyl esters. The results of the fatty acid compositions showed that NO had a higher amount of n-3 and n-6 polyunsaturated fatty acid (PUFA), particularly eicosapentaenoic acid (EPA) (C20:5). CG was predominantly high in palmitic acid (C16:0) and palmitoleic acid (C16:1). The extraction method 1 (dichloromethane:methanol) and extraction method 2 (water: propan-2-ol: hexane) with acetyl chloride-catalyzed transmethylation were found to be the best methods for the determination of fatty acid compositions in NO and CG, respectively. A significantly higher (P<0.05) amount of carotenoids was found in NO as compared to CG using different extraction methods. Extraction method 1 (involving saponification procedure) yielded the best result for NO while extraction method 3 (methanol: tetrahydrofuran with no saponification procedure) generated higher amounts of carotenoids in CG. Overall, this study has shown that significantly high amounts of fatty acids and carotenoids could be obtained from these microalgae using these methods.